Kontribusi Nilai Islam Pada Program Instalasi Pengelolaan Air Limbah Berbasis Masyarakat Di Lingkungan 01 Kelurahan Tanah Seribu - Padilla, Syindi Putri; Tanjung, Muaz (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Disposal of waste water which is a basic sterilization to oblige the kitchen to waste water and other waste. Seepage water drainage channels are very important, because waste water drainage channels can also limit the spread of disease to the local area. The aim of this research is to see the contribution of Islamic values ​​to the community-based wastewater management installation program in the 01 Tanah Seribu Village environment. This research uses a qualitative research method with a descriptive approach. Results of research on Islamic quality commitment to regional-based water waste by implementers of climate development programs in Tanah Seribu District 01, with details: 1) Viability is considered not yet ideal because the implementation of water content quality testing is not optimal because it does not pay attention to needs and the KPP's lack of attention to support WWTP. 2) The productivity of IPAL construction is considered large because it receives financial assistance from the APBN. However, functional expenditure is not yet ideal due to low regional support. 3) The arrangement should be ideal considering that the benefits of the program are mostly felt by the local area. 4) Adequacy is ideal because the IPAL program has many benefits. 5) Responsiveness regarding public reactions is considered certain, but open attitudes are still lacking. 6) Precision is not in accordance with Islamic qualities because there is no public awareness, but it is considered ideal because it tends to be the answer to the defeat of the water waste problem. Based on Islamic values, it can be concluded that the IPAL program in Environment 01, Tanah Seribu Subdistrict is in line with Islamic values ​​as seen in terms of environmental cleanliness which is increasingly maintained. However, on the other hand, community participation is still less than optimal in being responsible for protecting and preserving the environment.